A conceptual framework for the ethical deployment of Artificial Intelligence in addressing mental health challenges: Guidelines for Social Workers - Molala, Thomas; Makhubele, Jabulani (Technium Social Sciences Journal, 2021)
The deployment of Artificial Intelligence (AI) technologies has great potential to address mental health challenges-However there are great ethical challenges associated with AI. Purpose of the study: This study aims to develop conceptual ethical guidelines for Social Workers using AI in tackling mental health challenges. Methodology: The methodology employed in this paper is literature review-specifically an Integrative literature review of all sources related to the topic under investigation Main findings: The paper has found that the use of AI possesses the following ethical concerns: risk to privacy, loss of autonomy and biasness. The paper has further found that ethical guidelines for Social Workers using AI in addressing mental health challenges- should include protection laws, the use of approved AI technologies for which there are accountability standards, and training on the use of technology. Applications of this study: To this end, these guidelines will enable Social Workers to provide ethically sound AI-driven Social Work Services in dealing mental health challenges. Novelty/Originality of this study: Ethical concerns pertaining to the use of AI affect all helping professionals, therefore the ethical guidelines provided in this paper are expected to assist allied professionals navigate ethical paradoxes.